1995
DOI: 10.1088/0264-9381/12/12/019
|View full text |Cite
|
Sign up to set email alerts
|

Regge calculus as a fourth-order method in numerical relativity

Abstract: The convergence properties of numerical Regge calculus as an approximation to continuum vacuum General Relativity is studied, both analytically and numerically. The Regge equations are evaluated on continuum spacetimes by assigning squared geodesic distances in the continuum manifold to the squared edge lengths in the simplicial manifold. It is found analytically that, individually, the Regge equations converge to zero as the second power of the lattice spacing, but that an average over local Regge equations c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(30 citation statements)
references
References 11 publications
2
28
0
Order By: Relevance
“…Our numerical studies, together with analytic results [4] should put to rest some of the recent concerns about Regge calculus [5,6,7] -it does appear to be a viable approximation to general relativity.…”
Section: Regge Calculus As An Independent Tool In General Relativitymentioning
confidence: 95%
“…Our numerical studies, together with analytic results [4] should put to rest some of the recent concerns about Regge calculus [5,6,7] -it does appear to be a viable approximation to general relativity.…”
Section: Regge Calculus As An Independent Tool In General Relativitymentioning
confidence: 95%
“…Brewin [4] and M. Miller [5] have both developed their own schemes for averaging the Regge equations. A direct assault on the convergence properties of Regge calculus is therefore likely to be applicable only on a specific lattice, with a particular choice of averaging in the continuum limit.…”
Section: Investigating the Convergence Of Regge Calculusmentioning
confidence: 99%
“…It is this residual, using an appropriately chosen norm, which both Brewin and M. Miller considered [4,5]. Brewin observed that the residual of the simplicial equations remained roughly constant as the lattice was refined on a fixed region of spacetime.…”
Section: Investigating the Convergence Of Regge Calculusmentioning
confidence: 99%
See 1 more Smart Citation
“…In practice we imagine modified Regge calculus graphs with greatly simplifying assumptions would be used as approximations of the exact Regge calculus graph (also true of standard Regge calculus, obviously). When all link lengths are small, i.e., in the absence of disordered locality, these approximate Regge calculus solutions would then correspond to GR solutions and we have standard Regge calculus [48][49][50]. As with GR solutions, Regge calculus solutions are nontrivial and there is no reason to believe that finding extrema of a Regge graphical action modified per disordered locality would be any easier.…”
Section: The Modelmentioning
confidence: 99%